Molecular cloning and characterization of partial cDNA encoding for alpha-amylase inhibitor from kelampayan (neolamarckia cadamba) - Yong, L.F (University Malaysia Sarawak, UNIMAS., 2013)
Pest and pathogen infections are the main problems faced by forest plantations. Plants have developed pest resistance during evolution to enable it to survive. One of the natural protective mechanisms is known as alpha-amylase inhibitors. Alpha-amylase inhibitors function to inhibit the activities of alpha-amylase located in the insect’s gut. Neolamarckia cadamba or also known as Kelampayan is selected as the tree species due to its fast growth rate and wide range of usage and values. Besides that, no research has been done to identify the presence of alpha-amylase inhibitor gene in N. cadamba. The objective of this study was to clone and characterize the partial cDNA encoding alpha-amylase inhibitor from N. cadamba. Total RNA was isolated from developing xylem tissues and leaves. Total RNA was reversed transcribed into cDNA through RT-PCR. The purified PCR product was then sent for sequencing. Good sequencing data was not obtained and thus BLASTn cannot be performed to identify the identity of the gene.